Identification of novel SNPs in INHBB gene of Indian goat - SHARMA, REKHA; MAITRA, A; AHLAWAT, SONIKA; ROY, MANORANJAN; MANDAKMALE, S; TANTIA, M S (The Indian Journal of Animal Sciences, 2015)
Inhibin ï¢B (INHBB) gene is considered as a possible candidate gene for the prolificacy trait based on the important role of inhibin in reproduction. A mutation (A782G) in exon 2 of INHBB gene has significant effect on litter size in Jining Grey goats. Thus the objective of the present study was to explore polymorphism (SNP) in exon 2 region of INHBB in a panel of Indian goats consisting of high, medium and low prolificacy goat breeds. Two pairs of primers, P1 and P2 were designed according to the exon 2 sequence of bovine INHBB with amplified product size of 244bp and 296bp respectively. Polymerase chain reaction followed by direct DNA sequencing revealed absence of already reported SNP (A782G) in Indian goats where favorable A allele was fixed. Two novel SNPs were identified in the amplified products of primer P2 in Indian goats. These included Gï‚®A mutation at base 693 and Cï‚®T mutation at base 840 of exon 2 (numbering is with respect to U16241 sequence) in Indian goats, which did not cause any amino acid change. Allele distribution was of similar magnitude in Indian goats with predominance of wild allele (G=0.93 and C=0.96). Heterozygote was observed for G693A mutation in one animal each of Beetal, Osmanabadi, Sangamneri and Ganjam breeds, however heterozygotes of C840T mutations were observed in 4 animals of Osmanabadi breed only. Novel SNPs need further investigations for association with prolificacy trait that would have important implications for the goat industry.